2017
DOI: 10.1007/s00268-017-4309-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the Cost of Free Cleft Surgery in the Middle East?

Abstract: We conclude that 250 USD underestimates the actual costs to perform a single cleft surgery in Palestine and Sudan. If international cleft organizations are genuinely committed to creating sustainable international cleft programs, they should focus exclusively on training local professionals to perform surgery in hospitals of their own choosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…There have been few attempts by local teams in LMICs to assess the costs of CLP repair. 29 We performed a comprehensive audit of all supplies expended, staff fees, and facility expenses for patients who received cleft lip surgery at our institution in the last year of the study period. Our findings suggest that in our context where there is no surgeon fee and hospital fees are at cost, the greatest expense contributing to the surgery cost is consumable materials, specifically the sutures used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few attempts by local teams in LMICs to assess the costs of CLP repair. 29 We performed a comprehensive audit of all supplies expended, staff fees, and facility expenses for patients who received cleft lip surgery at our institution in the last year of the study period. Our findings suggest that in our context where there is no surgeon fee and hospital fees are at cost, the greatest expense contributing to the surgery cost is consumable materials, specifically the sutures used.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few attempts by local teams in LMICs to assess the costs of CLP repair 29 . We performed a comprehensive audit of all supplies expended, staff fees, and facility expenses for patients who received cleft lip surgery at our institution in the last year of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…19 One example by Sheriff et al showed that the average cost of cleft surgery in the Middle East was the most expensive when conducted by international nonprofit organizations, and the primary reason was the cost of travel. 43 This illustrates that although global surgery is deemed cost effective, it is much more expensive when done by international influences when the local area has its own capacity to perform surgeries. On the contrary, virtual consultation requires low cost and time commitments for expert surgeons in high-income nations.…”
Section: Why Plastic Surgery Needs Virtual Education In Lmicsmentioning
confidence: 99%